2002
DOI: 10.1007/s00232-001-0150-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation by Ca2+, ATP and Caffeine of Cardiac and Skeletal Muscle Ryanodine Receptors after Block by Mg2+

Abstract: The block of rabbit skeletal ryanodine receptors (RyR1) and dog heart RyR2 by cytosolic [Mg2+], and its reversal by agonists Ca2+, ATP and caffeine was studied in planar bilayers. Mg2+ effects were tested at submaximal activating [Ca2+] (5 microM). Approximately one third of the RyR1s had low open probability ("LA channels") in the absence of Mg2+. All other RyR1s displayed higher activity ("HA channels"). Cytosolic Mg2+ (1 mM) blocked individual RyR1 channels to varying degrees (32 to 100%). LA channels had r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 0 publications
5
45
0
Order By: Relevance
“…This was also first shown in skinned fibers and then in FSR (50,54,55,110,118,168,171,181,182,191). The order of potency was ATP ϳ adenosine 5Ј-(␤,␥-methylene)triphosphate (AMPPCP) Ͼ ADP ϳ cAMP Ͼ AMP Ͼ adenine Ͼ adenosine (54,118,168,181 are markedly increased by ATP and its analogs in the same manner (32,96,143,144,182,199,213). An interesting finding was that adenine and adenosine inhibit CICR in the presence of ATP.…”
Section: Potentiatorsmentioning
confidence: 70%
See 1 more Smart Citation
“…This was also first shown in skinned fibers and then in FSR (50,54,55,110,118,168,171,181,182,191). The order of potency was ATP ϳ adenosine 5Ј-(␤,␥-methylene)triphosphate (AMPPCP) Ͼ ADP ϳ cAMP Ͼ AMP Ͼ adenine Ͼ adenosine (54,118,168,181 are markedly increased by ATP and its analogs in the same manner (32,96,143,144,182,199,213). An interesting finding was that adenine and adenosine inhibit CICR in the presence of ATP.…”
Section: Potentiatorsmentioning
confidence: 70%
“…In addition to Mg 2ϩ , monovalent cations competitively antagonize Ca 2ϩ at the CICR A-site (169). 1 In the case of the high-activity RyR channels, Mg 2ϩ is reported to not completely inhibit Ca 2ϩ release by ATP in the absence of Ca 2ϩ (32). However, because the high-activity channels may not be in the physiological state as discussed in sect.…”
Section: Inhibitorsmentioning
confidence: 99%
“…36 and 44). Unlike previous tests (17,55), the solutions utilized in our planar lipid bilayer experiments contained the endogenous RyR2 modulators ATP and Mg 2ϩ (12), which allowed better comparison with cellular experiments. We tested channels exposed to resting Ca 2ϩ levels (100 nM), which opened infrequently (P o Ͻ 0.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Ca 2ϩ -release experiments (32) and bilayer experiments (12) found that there is a significant RyR1-mediated Ca 2ϩ leak under ionic conditions that mimic those in resting skeletal cells. This suggests that negative control is essential to prevent SR Ca 2ϩ depletion in resting fibers.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, caffeine (10 -3 mol/L) was used to activate RyR2-mediated Ca 2+ release from the SR. As a classic RyR agonist, caffeine can activate all RyR isoforms without selectivity at concentrations above 5×10 -3 mol/L [22][23][24] , but 10 -3 mol/L of caffeine activates RyR2>RyR1 [24] and RyR3>RyR1 [25] , and can increase the frequency of Ca 2+ spark [26] . In addition, Ca 2+ release induced by caffeine is positively related to the expression of RyR2, whereas it is negatively related to the expression of RyR3 [27] .…”
Section: Discussionmentioning
confidence: 99%